Configuração identitária do enfermeiro da estratégia de saúde da família de um município do interior do Estado de Minas Gerais - Glaucia de Sousa Vilela (2014)
VILELA, G. de S. Identity configuration of nurses of the family health strategy of a municipality in the state of Minas Gerais. 2014. 135 f. Dissertation [Masters in Nursing] School of Nursing, University of Minas Gerais, Belo Horizonte, 2014. Considering the assumptions about the construction of social identity and the organizational, structural, ideological challenges enrolled in the current scenario of the healthcare model in Brazil this study was emerged which aimed to understand the configuration of nurses identity of the family health strategy of a municipality in the state of Minas Gerais. For that, it was used a methodology of qualitative approach, choosing as a strategy for data collection a guided interview guided by a semi - structured interview. Data analysis followed the assumptions concerning content analysis, organized by theme. The setting of the research was the city which is located in the state of Minas Gerais, with a four teams of family´s health strategy. So, after acceptance of the invitation signing and the informed consent (IC), participated in this research twenty one subjects, stratified for analysis of nuclear subjects (four nurses) and secondary subjects (four auxiliary nursing four agents Community health, physician, primary care coordinator, a municipal health officer, five users of the service, a dentist). Data from the interviews were treated considering the configuration of the social identity of the nurse in the face of the characterization of virtual identity - obtained by analyzing the speech of secondary subjects - and the real identity of nurses - obtained by analyzing the speeches of the nuclear subject - culminating in shaping the identity configuration of nurses from this city of family health strategy. Data analysis allows us to understand that the identity of such configuration nurses is complex and in constant reconstruction and has determinant factors such as satisfaction and appreciation at work, the facilitating and hindering factors in service to the organization, infrastructure and ongoing education of staff and community; interference from politicians in daily staff , maintenance of centered medical model and incipient actions for the promotion of health, interpersonal relationships between staff - user - management, and the establishment of a bond between the team and community so that the care becomes effective.